2008
DOI: 10.1111/j.1365-2435.2008.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental, metabolic and immunological costs of flea infestation in the common vole

Abstract: Summary 1.Parasites use resources from their hosts, which can indirectly affect a number of host functions because of trade-offs in resource allocation. In order to get a comprehensive view of the costs imposed by blood sucking parasites to their hosts, it is important to monitor multiple components of the development and physiology of parasitized hosts over long time periods. 2. The effect of infestation by fleas on body mass, body length growth, haematocrit, resistance to oxidative stress, resting metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Nevertheless, the immune effort by itself does not shorten the life span of common voles (Devevey et al 2009). Moreover, rodents parasitized by fleas are immuno-depressed (Devevey et al 2008 ;Goü y de Bellocq et al 2006), and this makes them more sensitive to diseases. Alternatively, the spleen may also act as an erythropoietic organ in microtines (Watkins et al 1991), and thus splenomegaly observed in this study could be due to a combined effect of immune activation and the necessity to produce new red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the immune effort by itself does not shorten the life span of common voles (Devevey et al 2009). Moreover, rodents parasitized by fleas are immuno-depressed (Devevey et al 2008 ;Goü y de Bellocq et al 2006), and this makes them more sensitive to diseases. Alternatively, the spleen may also act as an erythropoietic organ in microtines (Watkins et al 1991), and thus splenomegaly observed in this study could be due to a combined effect of immune activation and the necessity to produce new red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are multiple studies demonstrating individual-level impacts of ectoparasites on hosts, with most research conducted on fleas. In laboratory studies, fleas were found to affect body condition, growth rate, life span, and energy expenditure of their hosts (e.g., Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009. In free-living animals, ectoparasites influenced host energy budgets (Giorgi et al 2001, Nilsson 2003, Kam et al 2010, litter size (Neuhaus 2003), foraging and vigilance patterns (Scantlebury et al 2007, Raveh et al 2011, and juvenile survival (Hawlena et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…A host defends itself against parasites using behavioural and/or immunological tools both of which incur substantial energetic (Sheldon and Verhulst 1996;Giorgi et al 2001;Schmid-Hempel and Ebert 2003;Devevey et al 2008) and subsequent fitness costs (Hanssen et al 2004). This may be especially true when a host is subjected to multiple parasite challenges (Taylor et al 1998).…”
Section: Introductionmentioning
confidence: 99%